2020
DOI: 10.1192/bjp.2020.242
|View full text |Cite
|
Sign up to set email alerts
|

Mental health before and during the COVID-19 pandemic in two longitudinal UK population cohorts

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic and mitigation measures are likely to have a marked effect on mental health. It is important to use longitudinal data to improve inferences. Aims: To quantify the prevalence of depression, anxiety and mental wellbeing before and during the COVID-19 pandemic. To identify groups at risk of depression and/or anxiety during the pandemic. Methods: Data were from two generations of the Avon Longitudinal Study of Parents and Children (ALSPAC): the index gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
420
7
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 419 publications
(483 citation statements)
references
References 55 publications
50
420
7
6
Order By: Relevance
“…Using survey data, one study found that socioeconomic deprivation was associated with higher risks of depression and anxiety disorders in adults and young people during the COVID-19 pandemic compared with pre-pandemic levels. 11 The inverse care law, which describes the combination of greater health care need among people living in deprived areas and the lack of additional availability of health services in these areas to meet increased demand, 28 has previously been demonstrated in relation to primary care management of self-harm, with lower referral rates associated with higher incidence and higher levels of deprivation. 29 Our findings suggest that COVID-19 has widened such inequalities, and have implications for general practices in deprived areas managing potential demand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using survey data, one study found that socioeconomic deprivation was associated with higher risks of depression and anxiety disorders in adults and young people during the COVID-19 pandemic compared with pre-pandemic levels. 11 The inverse care law, which describes the combination of greater health care need among people living in deprived areas and the lack of additional availability of health services in these areas to meet increased demand, 28 has previously been demonstrated in relation to primary care management of self-harm, with lower referral rates associated with higher incidence and higher levels of deprivation. 29 Our findings suggest that COVID-19 has widened such inequalities, and have implications for general practices in deprived areas managing potential demand.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from self-report surveys indicates that short-term increases in the prevalence of mental illness, self-harm, and suicidal ideation might have occurred after implementation of the UK lockdown in March, 2020. 8 , 9 , 10 , 11 Such increases are concerning because non-fatal self-harm is a strong risk factor for suicide. 4 , 12 Direct comparison of prevalence of mental health disorders before and after the COVID-19 pandemic is challenging; however, available evidence indicates that, to date, the prevalence of anxiety and depression during the pandemic has been higher than would be expected for the general population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcomes can also categorize individuals as having either poor mental health in a particular domain or not (Kwong et al, 2020). We fit logistic regression models with these outcomes, which give the odds of having poor mental health or wellbeing depending on degree of adherence.…”
Section: Resultsmentioning
confidence: 99%